2003
DOI: 10.1590/s0102-69922003000100012
|View full text |Cite
|
Sign up to set email alerts
|

Ciência, cognição e informação na operacionalização da gestão participativa da água no Brasil

Abstract: Resumo: A aprovação da Lei da Água no Brasil (Lei nº 9.433/ 97) não garantiu a sua operacionalização, incluindo o princípio da gestão participativa nas instâncias dos organismos de bacia (Comitês de Bacia Hidrográfica). Este trabalho aborda a importância da consideração conjunta de conhecimentos científicos e vivenciais, bem como da organização de uma sociedade da informação em rede, para a viabilização deste processo. Aspectos como capacitação dos decisores, visão sistêmica, subjetividade, valores, percepções… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
0
3
0
2
Order By: Relevance
“…Nesse caso, por exemplo, o referencial do desenvolvimento sustentável, proveniente da revolução científica ambiental, foi primordial na determinação dos quadros e das práticas socialmente legitimadas no instante da elaboração da política de recursos hídricos. Desde então, têm se tornado comuns as ideias de busca da sustentabilidade do uso da água a partir da gestão racional da demanda por meio de instrumentos regulamentares, participativos e econômicos (MAGALHAES JR;NETTO, 2003).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Nesse caso, por exemplo, o referencial do desenvolvimento sustentável, proveniente da revolução científica ambiental, foi primordial na determinação dos quadros e das práticas socialmente legitimadas no instante da elaboração da política de recursos hídricos. Desde então, têm se tornado comuns as ideias de busca da sustentabilidade do uso da água a partir da gestão racional da demanda por meio de instrumentos regulamentares, participativos e econômicos (MAGALHAES JR;NETTO, 2003).…”
Section: Discussionunclassified
“…Nessa perspectiva, a bacia ________________________________________________________________________________________________________ _______________________________________________________________________________________________________________ ParaOnde! ?, Porto Alegre, v.17, n.1, p.125-147, 2023. http hidrográfica como unidade de planejamento surge como uma nova escala de desenvolvimento para o local, ao mesmo tempo em que os atores mobilizados, em todas as suas diversidades, articulam as suas ações em favor dos recursos hídricos, a partir de seu valor ambiental, como um bem público e de uso comum de todos (MAGALHAES JR;NETTO, 2003).…”
Section: Discussionunclassified
“…During the period studying the samples (from November, 2012 to July, 2013), according to SIMEPAR (Meteorological System of Paraná), 2012/2013, there was a huge seasonal variation when collecting (figure 1); in July (2013) the climate was very dry, with a below-average precipitation index; in February and June (2013), on the other hand, it was extremely rainy, and in May (2013) and November (2012) the precipitation index was within the average. This is the reason why the standard deviation of most analyzes was not considered satisfactory (MAGALHAES JR and NETTO, 2003;MARQUES et al, 2017).…”
Section: Rainfall Datamentioning
confidence: 99%
“…Therefore, there was a water crisis in the late twentieth century, which motivated the search for solutions concerning the rational use of natural resources. Under these circumstances, the environmental management of water has shown great importance in the public policies of several countries, including Brazil (XUE et al, 2017;MAGALHAES and NETTO, 2003). In addition, some historical facts have also shown that some of the most widespread epidemics that have already afflicted human populations have their origins in water distribution systems.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there was a water crisis in the late twentieth century, which motivated the search for solutions concerning the rational use of natural resources. Under these circumstances, the environmental management of water has shown great importance in the public policies of several countries, including Brazil (XUE et al, 2017;MAGALHAES and NETTO, 2003). In addition, some historical facts have also shown that some of the most widespread epidemics that have already afflicted human populations have their origins in water distribution systems.…”
Section: Introductionmentioning
confidence: 99%